2017
DOI: 10.1021/acs.inorgchem.7b00027
|View full text |Cite
|
Sign up to set email alerts
|

Cationic and Neutral Cp*M(NO)(κ2-Ph2PCH2CH2PPh2) Complexes of Molybdenum and Tungsten: Lewis-Acid-Induced Intramolecular C–H Activation

Abstract: Treatment of CHCl solutions of Cp*M(NO)Cl (Cp* = η-C(CH); M = Mo, W) first with 2 equiv of AgSbF in the presence of PhCN and then with 1 equiv of PhPCHCHPPh affords the yellow-orange salts [Cp*M(NO)(PhCN)(κ-PhPCHCHPPh)](SbF) in good yields (M = Mo, W). Reduction of [Cp*M(NO)(PhCN)(κ-PhPCHCHPPh)](SbF) with 2 equiv of CpCo in CH at 80 °C produces the corresponding 18e neutral compounds, Cp*M(NO)(κ-PhPCHCHPPh) which have been isolated as analytically pure orange-red solids. The addition of 1 equiv of the Lewis ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 26 publications
3
13
0
Order By: Relevance
“…As in 5, the P-terminus of the κ 2 -P,N-PCH-2-(3-Me-C 5 H 3 N) ligand formally derived from i Pr 2 PN is oriented such that it lies trans to the nitrosyl ligand. The H atom belonging to C11 has been located in a difference map, and its position is consistent with the existence of an sp 2 shown in Figure S32. The labeled bond lengths are in agreement with the alternating single and double C−C bonds of the resonance structure drawn in Scheme 3.…”
Section: ■ Results and Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…As in 5, the P-terminus of the κ 2 -P,N-PCH-2-(3-Me-C 5 H 3 N) ligand formally derived from i Pr 2 PN is oriented such that it lies trans to the nitrosyl ligand. The H atom belonging to C11 has been located in a difference map, and its position is consistent with the existence of an sp 2 shown in Figure S32. The labeled bond lengths are in agreement with the alternating single and double C−C bonds of the resonance structure drawn in Scheme 3.…”
Section: ■ Results and Discussionsupporting
confidence: 66%
“…For instance, the 31 P{ 1 H} NMR spectrum shows a singlet at 28.0 ppm with 183 W satellites ( 1 J PW = 427.9 Hz; Figure S15), a feature that is similar to that previously reported for Cp*W(NO)(κ 2 -dppe). 2 The IR spectrum of 3 exhibits a strong ν(NO) absorption at 1525 cm −1 , which is a manifestation of the significant electron density extant at the metal center that results, in turn, in significant W → NO backbonding.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We speculate that interaction of the TMS with the nitrosyl may enhance the electrophilicity of the allyl cation (through the tungsten), which would enhance its reactivity with the nitrile solvent. Previously we have shown that the nitrosyl ligand of WTp(NO)(PMe 3 )(cyclohexene) can be methylated with MeOTf, [14] and independently the Legzdins group has demonstrated this reactivity with similar tungsten‐nitrosyl systems and Lewis acids [21] . In absence of the TMS group, a purported protonation of the nitrosyl is apparently reversed by the addition of triethylamine and cyclization does not occur.…”
Section: Introductionmentioning
confidence: 93%